Integrated STEM as Problem-Solving Practices. (2nd January 2022) - Roberts, Thomas; Maiorca, Cathrine; Jackson, Christa; Mohr-Schroeder, Margaret
ABSTRACT: Mathematics is foundational to integrated science, technology, engineering, and mathematics (STEM) education. Problem solving is central to integrated STEM and to the individual disciplines as evidenced by the practice standards of each discipline (e.g., Standards for Mathematical Practice, Science and Engineering Practices, and Technology and Engineering Practices). We situate integrated STEM as problem-solving practices by synthesizing practice standards from each discipline into four integrated STEM practices: (1) use critical and creative thinking to define and solve problems, (2) collaborate and use appropriate tools to engage in iterative problem solving, (3) communicate solutions to problems based on evidence and data, and (4) recognize and use structures in real-world systems. The integrated STEM practices are critical components of high-quality STEM learning experiences that allow students to apply discipline specific content to authentic problems. When each and every student is provided access and opportunity to high-quality integrated STEM learning experiences, they understand how mathematics is used in the real world and have more favorable views of mathematics. Mathematics education research could use the integrated STEM practices to rigorously investigate calls for greater access, equity, and opportunities in teaching and learning mathematics in integrated STEM contexts.